A importância do controle financeiro nas empresas - Trombetta, Ari (2014)
This work presents a succinct approach to the study of the importance of financial planning that has to be done within a company so that it succeeds in all his life trajectory . The company studied was Tromar Building Materials, located in the city of Pato Branco - PR, for construction and prefabricated slabs materials segment, operating in the market for over ten years in which values the quality of its products and services. The principal and investigate whether the company adopts the basic principles of financial control within the organization and how to manage these procedures aim. A case study, where we opted for a direct interview with the manager of the company, document analysis and proposal for the company to adopt some chips for daily cash management , cash flow , control accounts payable and receivable was conducted bank and others, telling the manager the importance of their role in the decisions to be taken but based on concrete data for the development and obtain greater profits for the company.